Brecha del servicio de limpieza pública en el distrito del Callao, Perú - Rossell Taype, Carlos Enrique (2022)
The purpose of this research is to get to know the people’s satisfaction regarding the quality of the public cleaning service provided by the Provincial Municipality of Callao, for the year 2021. The methodology used was the data collection technique through surveys. The results showed that the surveyed population considers that they have a predominantly "fair" and "poor" quality level of the cleaning, sweeping and collection service. Regarding the level of cleanliness, respondents consider that parks and markets have an acceptable level. Meanwhile, neighbors rated the separated collection service as "very bad." In addition, more than 50% of surveyed people do not comply with their obligation to pay municipal taxes and this action affects tax collection in the Municipality of Callao, because it does not allow to cover all the expenses of providing public cleaning services. Finally, there is a service quality gap that the Municipality must attend to by implementing an adequate waste management plan and environmental awareness and education programs, so that people act responsibly and thus improve the level of public cleaning service.